Evaluation of Healthy Lifestyles and Their Impact on Cardiovascular Risk in Adults Without Cardiovascular Disease. EVA Study (Revista de Medicina Clinica, 2024)
Introduction: To know the healthy lifestyles (HL) in adults and the relationship with cardiovascular risk . Patients and methods: Cross-sectional study to estimate CVR, alcohol and tobacco consumption, adherence to meiterranean diet, Physical activity and sedentary time. Results: SCORE (4.17±6.10), with Framingham (11.80±13.00) and heart age was 2.98±10.13 years younger than chronological age. 50.1% did not drink, 82.0% did not smoke, 25.3% adhered to the Mediterranean diet, 49.7% performed more than 26 hours/week of physical activity, 41.7% walked more than 10,000 steps/day, 51.3% were less than 142 hours/week sitting and 40.5% had 3 or more HL. The CVR SCORE showed positive association with: alcohol (B=0.018), hours/sitting (B=0.078), and negative with: hours/physical activity (B=-0.077), steps/day (B=-0.009) and HL number (B=-0.516). The CVR with Framingham showed positive association with: alcohol (B=0.047), tobacco (B=0.118), hours/sitting (B=0.139), and negative with MEDAS SCORE (B=-0.614), hours/physical activity (B=-0.136) and HL number (B=-1.707). The CVR estimated with heart age showed positive association with: smoking (B=0.145) and hours/sitting (B=0.105), and negative with hours/physical activity (B=-0.103), with the number of steps per day (B=-0.023) and HL number (B=-1.137). Conclusion: The consumption of alcohol, tobacco and sitting time show positive association, the number of HL adherence to the Mediterranean diet and physical activity negative association with the CVR.
Keywords: Lifestyles; Mediterranean diet; Physical activity; Alcohol; Tobacco